(untitled) (Eurasian Journal of Ecology, 2018)
In this research work the first time conducted research on the effect of lead on the animal organism. It was shown that lead adversely affects the quality and quantity of blood and organs of animals, and also found that a high-performance carbon “Ingo-2” nanostructured nanoenterosorbent has good corrective properties, restores homeostasis and contributes to the compensatory-adaptive reactions. The paper was also investigated effects of lead on the morphology of the internal organs of the animal organism. When comparing the actions identified reversible pathological changes observed and lead to signs of hydropic, and then the protein dystrophy plethora of vessels, the appearance of certain inflammatory infiltrates. However, these changes are reversible, are compensatory-adaptive nature and disappear after a single exposure nanoenterosorbent “Ingo-2.” A study that nanoenterosorbent “Ingo-2” has a strong universal sorption properties. In the lumen of the gastrointestinal tract it can bind and excrete coming from outside and formed inside the toxic substances of different nature, including lead. The studies we were first identified particular mechanisms of action nanoenterosorbenta “Ingo-2” on the morphological and physiological performance of internal organs in animals. Based on the data obtained proved that nanoenterosorbent “Ingo-2” with a single fed to rats causes the tissues in the esophagus, stomach, heart, kidneys and liver minor changes morphophysiological compensatory and adaptive nature, which are short and completely reversible. Key words: chemical pollutants, enterosorption, ecological crisis, hematology, human ecology, heavy metals, industrial waste, lead, morphology, neinteresant “Ingo-2”.